196 IMP3/KOC1, a New Immunohistochemical Marker for Differentiating Classical Hodgkin Lymphoma and Nodular Lymphocyte Predominant Hodgkin Lymphoma From Diffuse Large B-Cell Lymphoma. (11th January 2018) - Zhang, Xiaohong; Tsang, Patricia
Abstract: Introduction: Classical Hodgkin lymphoma (CHL), nodular lymphocyte predominant Hodgkin lymphoma (NLPHL), and diffuse large B-cell lymphoma (DLBCL) are distinct hematopoietic neoplasms with unique clinicopathologic features. The neoplastic cells of these tumors may mimic one another, causing diagnostic dilemmas. While the immunohistochemical (IHC) profiles of these three neoplasms are different, they can overlap and compound the diagnostic challenges. LP cells and DLBCL share similar IHC profiles, and no distinct IHC marker has yet been reported to consistently distinguish between the two neoplasms. Recently, several new IHC markers for CHL have been reported, including an embryo/carcinoma marker known as insulin-like growth factor II mRNA-binding protein 3 (IMP3/KOC). Our objective is to investigate the expression of IMP3/KOC among CHL, NLPHL, and DLBCL, in order to establish a new IHC profile to effectively distinguish these neoplasms. Method: A total of 84 cases of CHL, 90 cases of DLBCL and 13 cases of NLPHL were retrieved from Geisinger Health System for IHC studies using commercial antibody from DAKO. Result: None of the CHL cases (0 of 84), while all cases of NLPHL (13 of 13) and DLBCL (90 of 90), expressed CD20. Interestingly, IMP3/KOC was positive in 64.3% of CHL (53 of 83) cases and 92.3% (12 of 13) of NLPHL. In contrast, none of the DLBCL cases (0 of 90) expressed IMP3/KOC1, including primary mediastinal large B-cell lymphomas and T-cell/histiocyte-rich large B-cell lymphoma (T/HRLBL). The traditional markers, CD15 and CD30, were positive in 62% (51/82) and 81% (68/84) of CHL cases, respectively. PAX5 was weakly positive in CHL (83.3%) and strongly positive in NLPHL (100%) and DLBCL (100%). Conclusion: A novel IHC marker, IMP3/KOC, combined with CD20, can play an important role in differentiating between CHL, NLPHL and DLBCL. In particular, IMP3/KOC1 holds promise for distinguishing between NLPHL and its mimickers.